Analysis of putative mucosal SHIV susceptibility factors during repeated DMPA treatments in pigtail macaques. Issue 5 (4th August 2015) - Butler, Katherine; Ritter, Jana; Ellis, Shanon; Henning, Tara R.; Montague, Jeltley; Zaki, Sherif; Garber, David; McNicholl, Janet M.; Kersh, Ellen N.
Abstract Background Depot‐medroxyprogesterone acetate (DMPA) has been associated in some studies with increased HIV susceptibility in women. We used a pigtail macaque model to document the effects of repeated DMPA treatments and their potential contribution to increased SHIV susceptibility. Methods Nine pigtails were administered 2.5, 1.5, or 0.5 mg/kg DMPA in study weeks one and four. Menstrual cycling, vaginal epithelial thickness, and other SHIV susceptibility factors were monitored for a mean of 24 study weeks. Results All DMPA treatments suppressed menstrual cycling and increased vaginal pH. The vaginal epithelium thinned naturally during baseline menstrual cycles (from mean of 351 to 161 μm in late‐luteal phase). Following DMPA, the non‐nucleated layer was temporarily absent. Two weeks post‐second DMPA injection, mean epithelial thickness was 53, 45, and 167 μm for the descending doses, respectively. Conclusions All animals showed temporal vaginal epithelial thinning with loss of the non‐nucleated layer, and vaginal pH changes post‐DMPA injections.